145k views
3 votes
2x-3 = -x+3 what does x equal

User Evaenrique
by
5.3k points

2 Answers

3 votes

Answer:

x = 2

Explanation:

2x - 3 = - x + 3

First, combine the like terms

(Don't forget to change the signs with you bring a number or variable from one side to another.)

2x + x = 3 + 3

Then, add or subtract.

3x = 6

Divide.

x = 2

Hope this helps!

User Zzn
by
5.2k points
0 votes

Answer:

Isolate the variable by dividing each side by factors that don't contain the variable.

x = 2

Hope this helps! :)

User Yeon
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.